The role of long non-coding RNA (lncRNA) nuclear paraspeckle assembly transcript 1 (NEAT1) in chronic periodontitis progression. Issue 2 (1st February 2022) - Zhang, Lei; Lv, Hui; Cui, Yongxin; Shi, Rongji
ABSTRACT: Long non-coding RNA nuclear paraspeckle assembly transcript 1 (NEAT1) is a novel pro-inflammatory factor in severe human diseases. Since inflammatory plays important roles in periodontitis progression, we aimed to explore the role of NEAT1 in chronic periodontitis (CP) in vitro. We established a periodontitis cell model was established by Porphyromonas gingivalis lipopolysaccharide (Pg-LPS)-induced periodontal ligament cells (PDLCs). Quantitative reverse transcription polymerase chain reaction (qRT-PCR) was performed to detect the expression of NEAT1, microRNA (miR)-200c-3p, and tumor necrosis factor receptor-associated factor 6 ( TRAF6 ). Cell viability, inflammatory factors, and protein expression of Bcl-2, Bax, and TRAF6 were analyzed by MTT, enzyme-linked immunosorbent assay, and Western blot. The target relationships among NEAT1, miR-200c-3p, and TRAF6 were predicted by the StarBase/TargetScan software, and further validated by dual-luciferase reporter assay. In this research, NEAT1 is up-regulated in CP tissues and periodontitis model group. Silencing of NEAT1 and over-expression of miR-200c-3p enhanced cell viability and repressed apoptosis in the periodontitis model group. NEAT1 targets miR-200c-3p, and miR-200c-3p further targets TRAF6 . MiR-200c-3p inhibitor or over-expression of TRAF6 reversed the promoting effect of NEAT1 knockdown on cell viability, and the inhibiting effects on inflammatory cytokines and cell apoptosis. Consequently, the silencing of NEAT1 inhibits inflammation and apoptosis via targeting miR-200c-3p/ TRAF6 axis, thereby contributing to alleviate the progression of CP. This finding could provide an underlying target for the treatment of CP.